Jerome Bruner on Literature: Concerning the Importance of Narratives for Education - Vedran Dizdarevikj (Ars Lamina Publications and Institute of Pedagogy, Faculty of Philosophy, Ss. Cyril and Methodius University of Skopje, 2023)
In this paper we are going to discuss the status that the cognitive psychologist and pedagogue Jerome Bruner gives to narratives (stories) and literature, especially the part that he thinks that they should play in the process of education. In the first part of the paper, we are going to discuss Bruner’s important distinction between the paradigmatic (or logico-scientific) and the narrative modes of thinking and knowing. In the second part, we are going to clarify this distinction furthermore, and we will discuss the specifics of the narrative mode of knowing, especially the important part that stories play in the subject’s construction of the worldview and his idea of the self. We will also discuss the importance of literature in the context of the narrative mode of knowing and thinking. In the third part we will delve deeper at the importance that Bruner gives to literature, talk about what, according to him, are its benefits, and how literature can be better implemented in the process of education. In writing this paper we will consult Bruner's extensive literature, but we will mainly focus on the following books: On Knowing: Essays for the Left Hand (1979), Actual Minds, Possible Worlds (1985), Culture of Education (1996) and Making Stories: Law, Literature, Life (2002).
Keywords: narrative, story, literature, education, learning